Konsep Pendidikan Maria Montessori dalam Mengembangan Potensi Motorik dan Bahasa Anak - Samsuniyah, Samsuniyah; Saputra, Angga (AL-HANIF: Jurnal Pendidikan Anak dan Parenting, 2021)
The purpose of this research is to find out the concept of Maria Montessori's thinking in developing children's physical motor and language potential. Based on the results of the study that in developing the potential of children according to Montessori, it can be done with various meaningful activities through various media in the surrounding environment but still paying attention to interests, and talents and in accordance with the child's development